Модель распределения теплового потока в теплообменнике аппарата искусственного кровообращения - Максименко, Виталий Борисович; Шлыков, Владислав Валентинович; Данилова, Валентина Анатольевна (НТУ "ХПИ", 2016)
Предложена 3D-модель распределения теплового потока в теплообменнике аппарата искусственного кровообращения, которая позволяет контролировать температуру крови на выходе теплообменника в условиях искусственного кровообращения. Геометрическая форма теплообменника в системе MSC Sinda представляет собой куб, который содержит греющий теплоноситель – воду и трубки с нагреваемым теплоносителем – кровью. Реализация модели распределения теплового потока в теплообменнике для аппарата искусственного кровообращения в системе MSC Sinda дает распределение температур на входе и выходе теплообменника.

The 3D-model of the distribution of the heat flow for device of cardiopulmonary bypass, which allows you to control the blood temperature at the outlet of the heat exchanger for cardiopulmonary bypass are purposed. The geometric shape of the heat exchanger in the MSC Sinda system is a cube that contains a heating medium – water and heated coolant tube – blood. Implementation of the heat flow distribution in the heat exchanger model for cardiopulmonary bypass in the MSC Sinda system gives the temperature distribution at the inlet and outlet of the heat exchanger. In accordance with the physical and computational model for the once-through design of the heat exchanger in the process of warming the blood decreases the amount of heat that is given to water. This result is consistent with the heat balance equation in the absence of counter-movement of coolant – water and blood in a heat exchanger for the device of cardiopulmonary bypass.
The model of distribution heat flow in the heat exchanger for device of cardiopulmonary bypass
Keywords: модель; тепловой поток; теплообменник; распределение температуры; MSC Sinda; model; heat flow; heat exchanger; temperature distribution